Unmanned Aerial Vehicle Control System - Rustamov I. Kh. (Scientific Trends, 2024)
This article analyzes the state of control systems for unmanned aerial vehicles (UAVs), and considers problematic issues. Tendencies in the development of UAV control system are highlighted. Conclusions are made about the efficiency of using UAVs with the corresponding level of development of control systems.
Keywords: Unmanned aerial vehicle (UAV), control systems, autonomous control, group control, technical vision system (TVS), equipment of radio-electronic warfare (ERW), technical vision (TV).